Marine Life 2030: building global knowledge of marine life for local action in the Ocean Decade. (19th May 2022) - Muller-Karger, Frank E; Canonico, Gabrielle; Aguilar, Claudia Baron; Bax, Nicholas J; Appeltans, Ward; Yarincik, Kristen; Leopardas, Venus; Sousa-Pinto, Isabel; Nakaoka, Masahiro; Aikappu, Akkeshi; Giddens, Jonatha; Heslop, Emma; et al.
Abstract: Marine Life 2030 is a programme endorsed by the United Nations Decade of Ocean Science for Sustainable Development (the Ocean Decade) to establish a globally coordinated system that delivers knowledge of ocean life to those who need it, promoting human well-being, sustainable development, and ocean conservation. It is an open network to unite existing and new programmes into a co-designed, global framework to share information on methods, standards, observations, and applications. Goals include realizing interoperable information and transforming the observation and forecasting of marine life for the benefit of all people. Co-design, sharing local capacity, and coordination between users of ocean resources across regions is fundamental to enable sustainable use and conservation. A novel, bottom-up networking structure is now engaging members of the ocean community to address local issues, with Marine Life 2030 facilitating the linkage between groups across different regions to meet the challenges of the Ocean Decade. A variety of metrics, including those proposed by the Group on Earth Observations, will be used to track the success of the co-design process.